1997
DOI: 10.1111/j.1475-4932.1997.tb00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Technological Catch‐Up and Economic Growth in East Asia and the Pacific*

Abstract: This paper examines factors contributing to the faster economic growth in East Asia relative to other APEC economies. A simple but popular model is applied using purchasing power parity income estimates. Contrary to the view recently advanced by Krugman, we find that productivity improvement was an important factor contributing to the rapid East Asian growth. For many East Asian economies such as Japan, Korea, Taiwan and Hong Kong, a large proportion of higher than average growth is attributable to technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 21 publications
3
15
0
1
Order By: Relevance
“…The result is generally consistent with that of Sarel (1996Sarel ( , 1997, Hobday (1995), Collins and Bosworth (1997), Drysdale and Huang (1997) and Chang and Luh (1999), that productivity growth is also a main source of output growth, and far more optimistic than the findings of Young (1992Young ( , 1995 and Lau (1994, 1995). For example, Young finds that Singapore's average TFP growth is minus 1.1 per cent (TP and TFP growth are the same since no inefficiency is assumed, Young 1995, p658); and consequently that all its output growth is exclusively due to capital accumulation.…”
Section: Growth Decompositionsupporting
confidence: 84%
“…The result is generally consistent with that of Sarel (1996Sarel ( , 1997, Hobday (1995), Collins and Bosworth (1997), Drysdale and Huang (1997) and Chang and Luh (1999), that productivity growth is also a main source of output growth, and far more optimistic than the findings of Young (1992Young ( , 1995 and Lau (1994, 1995). For example, Young finds that Singapore's average TFP growth is minus 1.1 per cent (TP and TFP growth are the same since no inefficiency is assumed, Young 1995, p658); and consequently that all its output growth is exclusively due to capital accumulation.…”
Section: Growth Decompositionsupporting
confidence: 84%
“…Liao et al (2007) identified two sides of the debate. Accumulationists believed that the increased use and accumulation of inputs (especially the investment) rather than the increases in productivity explains all growth; this was represented by Young (1992Young ( , 1994aYoung ( , 1994bYoung ( , 1995, Krugman (1994), Collins & Bosworth (1996), Drysdale & Huang (1997), Crafts (1999a, 1999b. Assimilationists argued that the answer to growth lies in the use of more efficient technology, represented by World Bank (1993), Sarel (1996Sarel ( , 1997, Nelson & Pack (1999).…”
Section: Model Resultsmentioning
confidence: 99%
“…Compared with other East Asian manufacturing sectors, there have been relatively fewer TFP studies on Hong Kong's manufacturing sector because most TFP studies involving Hong Kong have concentrated on the overall economy, for instance, Dowrick and Nguyen (1989), Kim and Lau (1994), Young (1992;, Sarel (1995), Drysdale andHuang (1997), andHsieh (1999;.…”
Section: Review On Hong Kong's Manufacturing Sectormentioning
confidence: 98%